Influence of climate change on the spread Newcastle Disease in Africa. A Critical Literature Review - Mwamberi, Alfonso Mwamberi (Journal of Climate Policy, 2022)
Purpose: Newcastle Disease is a disease that is virulently caused by a form of avian Paramyxovirus type-1 virus that affects the respiratory systems of wild birds and poultry. The overall objective of this study was to examine influence of climate change on the spread Newcastle Disease in Africa. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: This study concluded that that farmers should be encouraged to keep poultry chicken depending on their capacity. Thus, there is a need to capacitate farmers' knowledge and participate in decision-making. Most of the adaptation measures can reduce negative impacts of climate change such as improved breeding, use of improved feedings, and burying the infected chicken. However, adaptation was taken into account but there were some challenges faced by farmers such as high cost of vaccinations; inconsistent forecasts of Newcastle Disease spread; lack of training; lack of enough funds; lack of information facilities; drug resistance; ignorance of farmers; culture and misconceptions. Finally, farmers should take more precautions of using vaccines against Newcastle Disease. Unique Contribution to Theory, Policy and Practice: This study recommended that the national government should devolve and set up weather stations at local levels to help the community monitor and forecast changes in temperatures and rainfall to help them take precautions against adverse climatic events, known as a precautionary principle for community preparation. The devolved and national governments are urged to strategize and provide extension services to farmers periodically to create awareness and technical guidance on dealing with Newcastle disease such as handling and taking hygiene precautions.